Information Technology Risk Analysis In The Personnel Management Information System (SIMPEG) At The Salatiga City Education Office - Natasya Ribka Malonda; Augie David Manuputty (Jurnal Mantik, 2021)
The Personnel Management Information System is an information system owned by the Education Office that is useful for managing ASN personnel data in Salatiga City. SIMPEG is used as a reference for decision-making for agencies, for example in promotions, as well as joint salary increases. However, in the world of risk management, no matter how good the system is, there is always the possibility of risks that can threaten and disrupt the business processes that run in the use of the information system. Therefore, a risk analysis of IS/IT resources is needed that supports the management of the personnel management information system in the Education Office. By applying the ISO 31000:2018 framework, it is hoped that this risk analysis can minimize the possible risks that exist. The results of this risk analysis are in the form of recommendations for risk actions that are needed according to the priority level of risk from the risk data that has been analyzed. So it is hoped that in the future the Education Office can apply the recommendations for risk actions that have been analyzed in this study.